(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
This research was carried out to evaluate the inhibitory effect of acetonic, ethanolic, and chloroformic extracts of Evernia prunastri lichen with concentrations of (25, 50, 75, 100) mg/ml against the plant pathogenic fungus Alternaria alternata. , all extracts showed a clear inhibitory effect on the growth of fungal hyphae and spores germination of the studied species compared to the control. Acetonic extract showed a high inhibition effect on (100) mg / ml growth of fungal hyphae and spores germination by (100) % respectively compared to the control, followed by ethanolic extract, the inhibiton rates at the same concentration were (92.96)% for the growth of fungal hyphae and (100)% for inhibition of spores germination. While the chloroformic extract had the least effective it compared to the previous tow extracts when the concentration (100) mg / ml, the inhibitory ratio for fungal hyphae reached (67.04)% and (77.30)% for spores germination. The results of this study confirm that Evernia prunastri lichen extracts, especially acetonic extract, plays an important role in the inhibiting the plant pathogenic fungus Alternaria alternata, and therefore its extracts can be used as low-cost fungicide with free side effects.